Sex, Status of DPT Immunization, and Pnemonia Incidence among Children Under Five in Puskesmas Tanjung Baru East Baturaja District - Rini Camelia; Willy Astriana (Jurnal Sains Kesehatan, 2018)
Background Each year, over 2 million children die of pneumonia, it means that 1 in 5 people in the world under five die of pneumonia and almost all (99.9%) deaths from pneumonia occur in developing countries (least developed). Order to determine the relationship of sex and DPT immunization status with the incidence of pneumonia in children under five (ages 1-59 months) at Tanjung Baru sub-district Puskesmas UPTD East Balfour. Method This research use analytical survay with cross sectional approach. The study population was all children under five who seek treatment at the health center UPTD Tanjung Baru during the study, with a sample of 73 people. Data analysis using univariate analysis and bivariate analysis using distribution table and Chi-Square statistical test, with 95% confidence degree. Results univariate analysis, of 73 respondents obtained 26% of respondents who suffered from pneumonia and 74% who do not suffer from pneumonia, 28.8% of respondents with male sex and 71.2% of respondents with female sex, 12.3% Respondents with incomplete DPT immunization status and 87.7% of respondents with complete DPT immunization status. The bivariate analysis results indicate no relationship sex with pneumonia (p value 0.003) and there was a DPT immunization status relationship with the incidence of pneumonia (p value 0.008). Keywords:  DPT immunization status incidence of pneumonia, sex